Identifying the significant factors in treated water using binary logistic regression model : a class study in Perlis, Malaysia - Fatin Munawwarah Aziz (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2017)
The research objectives are to identify the correlation between water quality parameters (water pH, water temperature, chlorine residual) with TCM concentration in treated water ; to determine the significant mean differences of TCM between four district ; to identify the significant predictors on the probability of purified water using logistic regression model.